Analysis of Mineral Content in Pomegranate Juice by ICP-OES - Akpinar-Bayizit, Arzu (Asian Journal of Chemistry, 2010)
Along with olives, figs and grapes, pomegranates are among the first plants to have been cultivated by man. The perceived consumer value of pomegranate and its juice is due in large part to its scientifically supported health benefits. The fruit is believed to have significant effects for arteriosclerosis, cholesterol levels and cancer prevention. In this study, the mineral compositions of commercial 100 % pomegranate juices were determined. Although processing steps include clarification and filtration, the pomegranate juices were a good source for minerals such as potassium (1283.30 mg/L), calcium (107.53 mg/L), sodium (96.02 mg/L), phosphorus (76.54 mg/L) and magnesium (67.22 mg/L). The high mineral content of pomegranate juices could contribute to the total intake of these constituents in the human diet.